Barriers and enablers to vaccination in the ultra-orthodox Jewish population: a systematic review - Jacobson, Avraham; Spitzer, Sivan; Gorelik, Yanay; Edelstein, Michael (Frontiers in Public Health, 2023)
Background The Jewish Ultra-Orthodox (UO) population is an under-vaccinated minority group that has been disproportionally affected by outbreaks of vaccine-preventable diseases (VPD) such as measles and polio. Underlying reasons remain poorly characterized. We aimed to identify vaccination barriers and enablers in this population. Methods We systematically reviewed the literature (PROSPERO: CRD42021273001), searching Pub-med, Web of science, Medline, PsychNet and Scopus from 1995 to 2021 for quantitative and qualitative primary research in English. Studies published outside the date range, not including barriers or enablers, or that were non-primary research were excluded. We assessed included publications for quality and extracted relevant data based on the 5As taxonomy: access, awareness, affordability, acceptance and activation. Results We included nine qualitative and seven quantitative studies from the 125 studies identified. Access barriers included scheduling difficulties, inconvenient opening hours, and logistical difficulties related to having multiple young children. Acceptance barriers included safety concerns. Insufficient knowledge about the importance of vaccine and timely vaccination and the perception of being shielded from infections because of seclusion from wider society were key awareness barriers. Competing priorities, such as work and housework, were the main affordability barriers. Mainstream religious leadership’s support for vaccination was an enabler, although recent studies suggest their influence on vaccination behavior is decreasing and influence of anti-vaccination messages is growing. Discussion Barriers to vaccination among the UO were mainly logistical, with little religious framing. Safety and efficacy concerns were similar to those reported in the wider community. Decreasing influence of the traditionally pro-vaccine mainstream religious leadership and growing influence of anti-vaccination movements targeting the UO community are new phenomena that require close monitoring. Tailored interventions are required to protect the community and wider society against future VPD outbreaks. Systematic review registration PROSPERO: CRD42021273001.